Interstrain Variation of the Major Internal Structural Component (p30(gag)) of Two Murine Oncornaviruses: Comparative Immunochemical, Biochemical, and Biophysical Analysis - Burnette, W. Neal (1978)
The major internal structural protein (p30(gag)) of the Moloney leukemia virus and the endogenous Y-1 murine oncornavirus was examined for biochemical and biophysical manifestations of interstrain antigenic variation. Although the two viral proteins share murine group-specific antigenic determinants, the Y-1 virus p30 appeared to have both a lower relative number of such determinants and a decreased affinity at the cross-reactive sites for Moloney virus p30 monospecific antibodies. Further, immunological analysis indicated the presence of unique antigenic sites on the Moloney virus p30 not shared by the analogous Y-1 virus molecule. The two polypeptides copurified and had similar isoelectric points (pH 6.2 to 6.3) and sedimentation coefficients (2.47S). However, equilibrium sedimentation yielded a significant mass difference between the two proteins, 28,300 ± 600 and 31,000 ± 300 daltons for the Moloney and Y-1 virus molecules, respectively. Amino acid analysis indicated a concomitant increase in total residues for the Y-1 virus p30, although a number of residues appeared to have been conserved between the two viral proteins. Conformational studies and hydrodynamic calculations demonstrated marked secondary and tertiary structural differences; with the Y-1 virus p30 being an asymmetric prolate ellipsoid containing 27 to 28% α-helix and Moloney virus p30 being somewhat more spherical and possessing an α-helical content of 50 to 55%. Two-dimensional mapping of (125)I-labeled tryptic peptides of each p30 suggested that considerable sequence heterogeneity is responsible for many of the biophysical, biochemical, and immunochemical differences in these two analogous structural proteins.